Time-Resolved Imaging of Femtosecond Laser-Induced Plasma Expansion in a Nitrogen Microjet - Anna Gabriella Ciriolo; Rebeca Martínez Vázquez; Gabriele Crippa; Michele Devetta; Aldo Frezzotti; Daniela Comelli; Gianluca Valentini; Roberto Osellame; Caterina Vozzi; Salvatore Stagira (Applied Sciences, 2022)
We report on the study of ultrafast laser-induced plasma expansion dynamics in a gas microjet. To this purpose, we focused femtosecond laser pulses on a nitrogen jet produced through a homemade De Laval micronozzle. The laser excitation led to plasma generation with a characteristic spectral line emission at 391 nm. By following the emitted signal with a detection system based on an intensified charge-coupled device (ICCD) we captured the two-dimensional spatial evolution of the photo-excited nitrogen ions with a temporal resolution on the nanosecond time scale. We fabricated the micronozzle on a fused silica substrate by femtosecond laser micromachining. This technique enabled high accuracy and three-dimensional capabilities, thus, providing an ideal platform for developing glass-based microfluidic structures for application to plasma physics and ultrafast spectroscopy.